Early treatment and toxicity outcomes for small posterior uveal melanomas treated using custom loaded eye plaques - Medek, Sara; Correa, Zelia M.; Huth, Brad; Takiar, Vinita (Frontiers in Medicine, 2023)
Introduction Iodine-125 loaded Collaborative Ocular Melanoma Study plaques can achieve excellent tumor control for patients diagnosed with uveal melanomas. Our ocular cancer team hypothesized that use of novel, partially loaded COMS plaques could ease and improve accurate plaque placement during treatment of small, posterior tumors while providing equivalent tumor control. Materials/methods Records of 25 patients treated with custom plaques were compared to 20 patients treated with fully loaded plaques, who had received treatment prior to our institution’s adopting the use of these partial plaques. Tumors were matched with regards to location and dimensions as measured by the ophthalmologist. Retrospective analysis of dosing parameters, tumor control and toxicity outcomes were performed. Results There were no cancer related deaths, local recurrences or metastases in either cohort at an average follow up of 24 months for patients treated with custom plaques and 60.7 months for patients treated with fully loaded plaques. No statistically significant difference was found in regards to post-operative development of cataracts (χ2 = 0.76) or radiation retinopathy (χ2 = 0.22). Patients treated with custom loaded plaques noted significantly less clinical visual loss (χ2 = 0.006) and were more likely to have vision preserved at ≥20/200 (χ2 = 0.006). Conclusion Treatment of small, posterior uveal melanomas with partially loaded COMS plaques results in equivalent survival and recurrence outcomes as treatment with fully loaded plaques, while exposing the patient to less radiation. Additionally, treatment with partially loaded plaques reduces the incidence of clinically significant visual loss. These promising early results support the use of partially loaded plaques in well-selected patients.